The Effect of Casein Phosphopeptide-Amorphous Calcium Phosphate Containing Bonding Agents on Dentin Shear Bond Strength and Remineralization Potential: An in Vitro Study - Parniaan Karimi Yeganeh; Hosna Teimourian; Baharan Ranjbar Omidi; Faezeh Amiri; Mohammadreza Tahriri; Negin Farahmandpour (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess the effect of Casein Phosphopeptide-Amorphous Calcium Phosphate (ACP) containing bonding agents on dentin shear bond strength and remineralization potential. Material and Methods: This in vitro study evaluated 45 extracted human premolars. The teeth were decoronated, and the tooth crown was split into buccal and lingual halves. The specimens were then flat-grounded by a 180-grit abrasive. The specimens were then randomized into three groups (n=15). Adper Scotchbond Multi-Purpose (SBMP) primer and adhesive were used for bonding in the control group. ACP in 10wt% and 20wt% concentrations was added to SBMP adhesive and used in groups 2 and 3, respectively. After the application of primer and adhesive and light-curing them for 10 s, a transparent silicon cylinder was placed on a dentin surface and cured for 10 s; then, the cylinder was filled with composite resin and was cured for the 40s from each side. The specimens underwent 3000 thermal cycles, and a universal testing machine measured the SBS. To assess the remineralization quality, a total of 6 dentin samples (2 specimens for group) were prepared and underwent X-ray diffraction, attenuated total reflection Fourier-transform infrared spectroscopy, and scanning electron microscopy-energy dispersive X-ray analysis. One-way analysis of variance was used to analyze the data. The level of p<0.05 was considered significant. Results: No significant difference in dentin shear bond strength was noted between the groups (p>0.05) - the addition of ACP to SBMP adhesive enhanced dentin remineralization. Increasing the ACP concentration from 10% to 20% increased the formation of hydroxyapatite. Conclusion:Adding amorphous calcium phosphate confers remineralizing property to SBMP adhesive without compromising its shear bond strength to dentin.